The Rare Anaphylaxis-Associated FcγRIIa3 Exhibits Distinct Characteristics From the Canonical FcγRIIa1 - Anania, Jessica C.; Trist, Halina M.; Palmer, Catherine S.; Tan, Peck Szee; Kouskousis, Betty P.; Chenoweth, Alicia M.; Kent, Stephen J.; Mackay, Graham A.; Hoi, Alberta; Koelmeyer, Rachel; Slade, Charlotte; Bryant, Vanessa L.; et al. (Frontiers in Immunology, 2018)
FcγRIIa is an activating FcγR, unique to humans and non-human primates. It induces antibody-dependent proinflammatory responses and exists predominantly as FcγRIIa1. A unique splice variant, we designated FcγRIIa3, has been reported to be associated with anaphylactic reactions to intravenous immunoglobulins (IVIg) therapy. We aim to define the functional consequences of this FcγRIIa variant associated with adverse responses to IVIg therapy and evaluate the frequency of associated SNPs. FcγRIIa forms from macaque and human PBMCs were investigated for IgG-subclass specificity, biochemistry, membrane localization, and functional activity. Disease-associated SNPs were analyzed by sequencing genomic DNA from 224 individuals with immunodeficiency or autoimmune disease. FcγRIIa3 was identified in macaque and human PBMC. The FcγRIIa3 is distinguished from the canonical FcγRIIa1 by a unique 19-amino acid cytoplasmic insertion and these two FcγRIIa forms responded distinctly to antibody ligation. Whereas FcγRIIa1 was rapidly internalized, FcγRIIa3 was retained longer at the membrane, inducing greater calcium mobilization and cell degranulation. Four FCGR2A SNPs were identified including the previously reported intronic SNP associated with anaphylaxis, but in only 1 of 224 individuals. The unique cytoplasmic element of FcγRIIa3 delays internalization and is associated with enhanced cellular activation. The frequency of the immunodeficiency-associated SNP varies between disease populations but interestingly occurred at a lower frequency than previously reported. None-the-less enhanced FcγRIIa3 function may promote a proinflammatory environment and predispose to pathological inflammatory responses.